2016
DOI: 10.22230/cjc2016v41n1a2915
|View full text |Cite
|
Sign up to set email alerts
|

Explicating the Values-Issue Consistency Hypothesis through Need for Orientation

Abstract: The values-issues consistency hypothesis posits that when the issues covered in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…McCombs [22] demonstrated that the motivation for individuals to perceive an issue as significant can be attributed to emotional arousal. Empirical studies further confirmed that emotions indeed play a mediating role in agenda-setting, irrespective of the personal relevance of the issue [21]. For example, Young [23] argued that issues presented in the news were considered more important when they were perceived as fearful.…”
Section: Agenda-setting Theory and Emotionsmentioning
confidence: 87%
See 1 more Smart Citation
“…McCombs [22] demonstrated that the motivation for individuals to perceive an issue as significant can be attributed to emotional arousal. Empirical studies further confirmed that emotions indeed play a mediating role in agenda-setting, irrespective of the personal relevance of the issue [21]. For example, Young [23] argued that issues presented in the news were considered more important when they were perceived as fearful.…”
Section: Agenda-setting Theory and Emotionsmentioning
confidence: 87%
“…In addition, studies found that emotional reactions to news influence issue salience, mediating agenda-setting effects. Emotions can increase relevance and people may recognize that an issue is important even if it lacks personal or social relevance to them [21].…”
Section: Agenda-setting Theory and Emotionsmentioning
confidence: 99%